Assessment of extractable carbon and nitrogen mineralization in paddy soil under Fenton reaction - Nguyen Thi Linh, Phuong; Phan Xuan, Hoang; Le ngoc Hanh, Ngan; Nguyen Thi Thuy, Yen; Van Tran Duc, Huy; Pham Thanh, Vuong; Do Hong, Hanh; Tran Thi, Phu; Phan Thi, Thuy; Nguyen Sy, Toan (Hue University Journal of Science: Natural Science, 2025)
This study aims to evaluate the effects of straw, Fenton reagent, and the combination of straw and Fenton treatments on the decomposition of organic matter and nitrogen mineralisation in soil. Extractable carbohydrate, total dissolved organic carbon (DOC), ammonium (NH₄⁺) and nitrate (NO₃–) contents, and total inorganic nitrogen were analysed. The results show that the Fenton treatment significantly increased the NH₄⁺ content (23.65 mg/kg) and the inorganic-to-total-N ratio (20.30%), reflecting a strong mineralisation capacity. Meanwhile, the combined treatment resulted in the lowest NO₃– concentration, indicating potential nitrogen retention or loss. Principal component analysis (PCA) reveals a clear grouping among treatments, with DOC and NH₄⁺ being the key variables contributing to this grouping. These findings provide a scientific foundation for selecting appropriate treatment methods to enhance soil nutrient availability in agricultural systems.